A fresh (air) look at ventilation for COVID-19: Estimating the global energy savings potential of coupling natural ventilation with novel radiant cooling strategies. (15th June 2021) - Aviv, Dorit; Chen, Kian Wee; Teitelbaum, Eric; Sheppard, Denon; Pantelic, Jovan; Rysanek, Adam; Meggers, Forrest
Graphical abstract: Highlights: ASHRAE et al. recommends increasing indoor fresh air supply to mitigate COVID-19 spread. Increased fresh air supply may double energy costs when operating a conventional HVAC system. We propose an HVAC solution which couples novel radiant systems with natural ventilation. We estimate this solution would address thermal comfort needs in all major climate zones. Where adopted, this solution could reduce building HVAC energy demand by 10–45%. Abstract: Radiant cooling-assisted natural ventilation is an innovative technical approach that combines new radiant cooling technology with natural ventilation to increase fresh air delivery into buildings year-round with minimal energy cost and improvment of air quality. Currently, the standard paradigm for HVAC (heating, ventilation and air conditioning) is based on central air systems that tie the delivery of heating and cooling to the delivery of fresh air. To prevent heat loss, the delivery of fresh air must be tightly controlled and is often limited through recirculation of already heated or cooled air. Buildings are designed with airtight envelopes, which do not allow for natural ventilation, and depend on energy-intensive central-air systems. As closed environments, buildings have become sites of rapid COVID-19 transmission. In this research, we demonstrate the energy cost of increasing outdoor air supply with standard systems per COVID-19 recommendations and introduce an alternative HVAC paradigm that maximizes the decoupling of ventilation and thermal control. We first consider a novel analysis of the energy costs of increasing the amount of conditioned fresh air using standard HVAC systems to address COVID-19 concerns. We then present an alternative that includes a novel membrane-assisted radiant system we have studied for cooling in humid climates, in place of an air conditioning system. The proposed system can work in conjunction with natural ventilation and thus decreases the risk of indoor spread of infectious diseases and significantly lowers energy consumption in buildings. Our results for modeling HVAC energy in different climates show that increasing outdoor air in standard systems can double cooling costs, while increasing natural ventilation with radiant systems can halve costs. More specifically, it is possible to add up to 100 days' worth of natural ventilation while saving energy when coupling natural ventilation and radiant systems. This combination decreases energy costs by 10–45% in 60 major cities globally, while increasing fresh air intake.